Outcome differences in HPV-driven head and neck squamous cell carcinoma attributable to altered human leukocyte antigen frequencies - Wichmann, Gunnar; Vetter, Nathalie; Lehmann, Claudia; Landgraf, Ramona; Doxiadis, Ilias; Großmann, Rebecca; Vorobeva, Ekaterina; Dietz, Andreas; Zebralla, Veit; Wiegand, Susanne; Wald, Theresa (Frontiers in Oncology, 2023)
Background Effective immune surveillance requires a functioning immune system and natural killer (NK) and T cells for adequate innate and antigen-specific immune responses critically depending on human leukocyte antigens (HLAs) and haplotypes representing advantageous combinations of HLA antigens. Recently, we reported a link between altered frequencies of HLA alleles and haplotypes and developing head and neck squamous cell carcinoma (HNSCC). Whereas the majority of HNSCCs seem to be related to classical risk factors alcohol and tobacco, a subset of HNSCC and especially oropharyngeal squamous cell carcinoma (OPSCC) were etiologically linked to human papillomavirus (HPV) recently. Here, we demonstrate in HPV-driven (p16-positive high risk-HPV DNA-positive) HNSCC a deviating distribution of HLA antigens and haplotypes and their relevance to outcome. Methods Leukocyte DNA of n = 94 HPV-driven HNSCC patients (n = 57 OPSCC, n = 37 outside oropharynx) underwent HLA SSO typing, allowing allele, antigen (allele group), and haplo-typing. Besides comparing these frequencies with those of German blood donors, we analyzed their impact on outcome using Kaplan–Meier plots and Cox proportional hazard regression. Results Antigen and haplotype frequencies demonstrate enrichment of rare antigens and haplotypes. The HLA score for unselected HNSCC patients was not predictive for outcome here. However, together with alcohol consumption, tobacco smoking, T category, and extranodal extension of locoregional metastases and treatment applied, eight HLA traits allow for predicting progression-free and tumor-specific survival. Conclusion Patients can be categorized into low, intermediate-low, intermediate-high, and high risk groups. Using a new PFS risk score for HPV-driven HNSCC may allow to improve prognostication.